2003
DOI: 10.1523/jneurosci.23-04-01254.2003
|View full text |Cite
|
Sign up to set email alerts
|

blue cheeseMutations Define a Novel, Conserved Gene Involved in Progressive Neural Degeneration

Abstract: A common feature of many human neurodegenerative diseases is the accumulation of insoluble ubiquitin-containing protein aggregates in the CNS. Although Drosophila has been helpful in understanding several human neurodegenerative disorders, a loss-of-function mutation has not been identified that leads to insoluble CNS protein aggregates. The study of Drosophila mutations may identify unique components that are associated with human degenerative diseases. The Drosophila blue cheese (bchs) gene defines such a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
194
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(208 citation statements)
references
References 67 publications
(94 reference statements)
13
194
1
Order By: Relevance
“…bchs has extensive homology to ALFY throughout the entire sequence and consistent with the mouse tissue expression profile of ALFY (highest in the brain), 47 bchs seems to be selectively expressed in the fly brain. 85 Moreover, adult flies lacking bchs accumulate ubiquitin-positive inclusions and display a neurodegenerative phenotype, 73 in line with the proposed function of ALFY in autophagic degradation of aggregate-prone proteins. In a screen for genetic modifiers of a gain-of-function (GOF) rough eye phenotype caused by overexpression of bchs, the small GTPase Rab11 was found to enhance this phenotype.…”
Section: Alfy Homologssupporting
confidence: 62%
See 1 more Smart Citation
“…bchs has extensive homology to ALFY throughout the entire sequence and consistent with the mouse tissue expression profile of ALFY (highest in the brain), 47 bchs seems to be selectively expressed in the fly brain. 85 Moreover, adult flies lacking bchs accumulate ubiquitin-positive inclusions and display a neurodegenerative phenotype, 73 in line with the proposed function of ALFY in autophagic degradation of aggregate-prone proteins. In a screen for genetic modifiers of a gain-of-function (GOF) rough eye phenotype caused by overexpression of bchs, the small GTPase Rab11 was found to enhance this phenotype.…”
Section: Alfy Homologssupporting
confidence: 62%
“…Drosophila lacking the ALFY homolog bchs have a neurodegenerative phenotype characterized by accumulation of insoluble ubiquitin-positive inclusions in their brain and a reduced life span, 73 indicating that ALFY is important for degradation of aggregation-prone ubiquitinated proteins also in vivo. Confocal immunofluorescence and biochemical analysis revealed that ALFY forms a complex with polyQ protein-containing inclusions associated with Huntington's disease (HD).…”
Section: Alfy and Neurodegenerationmentioning
confidence: 99%
“…8 Over time these insoluble ubiquitinated proteins (IUP) form aggregates and become relatively insoluble cellular inclusions or proteopathies. 8,9 Genetic manipulation of key autophagy components often alters IUP profiles in neuronal tissues. [8][9][10][11][12] A second marker of aggregates, p62 also accumulates in cells when autophagy is inhibited.…”
Section: Ref(2)p Profiles Reflect Age-dependent and Genetic Changes Tmentioning
confidence: 99%
“…These defects are preceded by the accumulation of ubiquitin-conjugated protein aggregates throughout the adult CNS. 16 Consistent with these findings is the characterization of the bchs human homologue, Alfy. 17 Under starvation conditions Alfy colocalizes with cytoplasmic structures containing ubiquitin and early markers of the autophagic pathway.…”
Section: Introductionmentioning
confidence: 60%
“…17 Both Bchs and Alfy are large, highly conserved proteins containing functional domains associated with lysosomal transport and protein-protein and protein-lipid interactions (i.e., BEACH, WD40 and FYVE domains), indicating that these proteins may serve as molecular scaffolds able to mediate diverse interactions, which promote vesicle trafficking to the lysosome. 16,17 To further investigate potential bchs genetic interactions, we took advantage of the finding that overexpression of Bchs in the Drosophila eye using the Gal4/UAS system (GMR-Gal4 driver) produces an external rough eye phenotype. 18 We also detected ubiquitin-containing varicosities along the length of photoreceptor neural projections in Bchs-overexpressing eyes and found that young bchs mutants and overexpressing flies both show an altered profile of total ubiquitinated proteins.…”
Section: Introductionmentioning
confidence: 99%